The short bowel syndrome in children: peculiarities of etiopathogenesis, clinical signs and treatment (analysis of literature and own observations) - O. M. Gorbatyuk; A. S. Lavryk; V. V. Kucheruk (Клінічна хірургія)
The short bowel syndrome in children: peculiarities of etiopathogenesis, clinical signs and treatment (analysis of literature and own observations)